Temperature-driven migration of heavy metal Pb2+ along with moisture movement in unsaturated soils. (June 2020) - Bai, Bing; Xu, Tao; Nie, Qingke; Li, Pengpeng
Highlights: New scanning curve equations for SWCC are constructed according to the shape similarity with the boundary curves. Test results verify the hysteresis of moisture movement induced by thermal cycling. The temperature-driven migration of heavy metal Pb 2+ is well predicted. Abstract: Nonlinear coupled heat-moisture-contaminant transport equations are established to analyze the temperature-driven movement of moisture and migration of heavy metal Pb 2+ in unsaturated soils. A new soil–water characteristic curve (SWCC) with hysteretic effects is constructed, which can directly give the scanning curve equations starting from any point on the boundary curves without introducing a new equation or new parameters. The theoretical results demonstrate good agreement with the results of laboratory tests in a soil column and satisfactorily verify the hysteretic effects of moisture movement induced by thermal cycling. Due to the obvious driving effect of the temperature gradient, the moisture in the soil column gradually moves to a distant point and develops a nonuniform distribution. Finally, the driving potential of the temperature gradient and the driving potential of the moisture content gradient reach a new equilibrium. In addition to the flow of liquid water, the movement of moisture also includes the transformation of liquid water to water vapor. With the movement of moisture, the migration distance of heavy metal Pb 2+ increases with increasing initial moisture content. Generally, kaolin clay with a high adsorption capacity has an obvious retardation effect on the migration of heavy metal contaminants.